Model Adaptive Collaborative Governance In Extreme Poverty Alleviation In Pekalongan Regency - M. Yulian Akbar; Hardi Warsono; Teguh Yuwono; Bangkit Aditya Wiryawan (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Extreme poverty is a multidimensional public policy challenge that requires integrated and adaptive governance beyond sectoral government interventions. This study aims to develop an Adaptive Collaborative Governance Model for extreme poverty alleviation in Pekalongan Regency, Indonesia. A qualitative case study approach was employed to examine governance practices, stakeholder interactions, institutional arrangements, and adaptive capacities. Data were collected through interviews, focus group discussions, observations, and document analysis involving government agencies, village administrations, community representatives, academics, private sector actors, civil society organizations, and social facilitators. Data were analyzed using an interactive model of data condensation, data display, and conclusion drawing. The findings show that existing governance arrangements have established institutional structures, multi-sectoral programs, and stakeholder participation mechanisms. However, their effectiveness is constrained by fragmented poverty data, limited information integration, uneven participation, sectoral coordination, and weak policy learning processes. Collaborative governance has emerged through stakeholder engagement and coordination forums but remains largely administrative and insufficiently adaptive. Supporting factors include strong local government commitment, integrated planning, stakeholder engagement, data verification mechanisms, and the Poverty Laboratory as a collaborative platform. Key obstacles include fragmented information systems, overlapping programs, and limited community participation. Based on these findings, the study proposes an Adaptive Collaborative Governance Model integrating collaborative governance principles with adaptive governance capacities through the Poverty Laboratory. The model consists of integrated poverty data, collaborative platforms, community participation, economic empowerment, and adaptive learning. This study contributes to collaborative governance theory and offers a practical framework for sustainable extreme poverty alleviation at the local government level.